Risk Factors Analysis and Angiographic Profile in Postmenopausal Women with Coronary Artery Disease (Cardiovascular Journal, 2011)
Background : Postmenopausal women are at greater risk for coronary artery disease (CAD) than premenopausal women. This may be due to deprivation of estrogen, which acts directly and indirectly on the vasculature. In light of this finding the aim of the study was to find the relation of serum estrogen level with severity of atherosclerotic lesion and number of risk factors in CAD among postmenopausal women. Methods: One hundred postmenopausal women undergoing coronary angiography (CAG) were studied. Among them 50 patients with estrogen level 25 pg/ml constituted study Group II. Serum estrogen level was measured by radioimmunoassay. Other important risk factors like dyslipidaemia, diabetes mellitus, hypertension, family history of CAD, smoking and waist circumference were evaluated between the 2 groups of patients. CAG findings were analyzed by eye estimation and by Gensini score. Results: All the risk factors were significantly higher in Group I patients than that of Group II. Among the risk factors hypertension was most prevalent (64%) in Group I and dyslipidaemia (40%) in Group II. Multivariate regression analysis showed that serum estrogen was a strong and an independent predictor of CAD (p=0.001) when considered with other standard risk factors. Association between the angiographic severity of CAD and serum estrogen level were evaluated and negative correlation was observed, i.e. lower the serum estrogen level higher the vessel score. Conclusion: In postmenopausal women serum estrogen level is a strong & an independent predictor of CAD. It is also found that low estrogen group of postmenopausal women with CAD have more severe atherosclerotic lesions in comparison to the group with normal estrogen level. Keywords: Risk factor, Coronary artery disease, Postmenopausal women, Angiographic profile. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8235 Cardiovasc. j. 2009; 1(2): 161-164